Case Study in Indonesia: Does the Behavior of Online Transportation Service Drivers Influence Driver Operational Performance? - Adieb Rayhan; B. W. Bramantio; Erlangga Pranowo; Falih Rengga; Hanindito Herbowo (Jurnal Syntax Admiration, 2024)
This research invests the impact of ride-hailing driver behavior on the operational performance of drivers in Indonesia. Previous research in Texas, America (Idug, 2023) objectively research the preexisting impacts of a ride-hailing driver's operational performance. The research showed that there is a significant impact of the driver’s intention to comply with rules to the rating, acceptance rate and declination rate of the drivers. However, based on this study, further research is required in Indonesia to determine if the same variables are also significant to the driver understanding of a companies’ guideline of operation and their intentions to comply with the company’s rule thorugh a random sampling of 302 respondents. General deterrence theory, understanding resource vulnerability of information, protection motivation and intention to comply do not affect the rating, indicating bias in ratings, drivers acceptance affected by intention to comply and significant influence between protection motivation and cancellation rate, despite the drivers have an understanding of data vulnerabilities, fear of penalties and motivated to protect themselves it has no effect on how many orders they complete, Drivers tend to cancel the order to protect themselves. The result of this research have some unique findings on the ride-hailing operation dynamics in Indonesia, the relationship between drivers, rider, and system through ride-hailing platforms that have much insight for ride-hailing company management to be applied for performance improvement.